New record and geographic distribution map of Microcaecilia taylori Nussbaum and Hoogmoed, 1979 (Amphibia: Gymnophiona: Siphonopidae) with notes on size and natural history - Ângelo Dourado; Cândido Monteiro Junior; Adriano Maciel (Check List, 2011)
Microcaecilia taylori is known to occur from the Guianan region to south of the Amazon in the state of Pará, Brazil. Here we provide a new locality record for the species, east of the Tocantins River, 190 km from the nearest record. The specimen was active under the leaf litter in daylight and is the largest specimen of M. taylori recorded to date.